2005
DOI: 10.1186/1477-7819-3-47
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that the p53 negative / Bcl-2 positive phenotype is an independent indicator of good prognosis in colorectal cancer: A tissue microarray study of 460 patients

Abstract: Patient stratification by combined p53 / Bcl-2 phenotype provides stage-independent prognostic information in colorectal cancer. Specifically, that up to a quarter of patients display a good prognosis p53(-)/Bcl-2(+) phenotype. This may indicate a more clinically indolent phenotype and a subset of patients for whom less aggressive adjuvant treatment appropriate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 26 publications
1
13
0
1
Order By: Relevance
“…Expression of Bcl2 and p53 have previously been reported (Watson et al , 2005). As a marker of IFN- γ -induced activation, expression of MHC-II on tumour cells and stroma-associated cells was measured.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…Expression of Bcl2 and p53 have previously been reported (Watson et al , 2005). As a marker of IFN- γ -induced activation, expression of MHC-II on tumour cells and stroma-associated cells was measured.…”
Section: Resultsmentioning
confidence: 81%
“…The study population comprised a series of 462 consecutive patients undergoing elective surgical resection of a histologically proven sporadic primary colorectal cancer at the University Hospital, Nottingham, UK (Table 1; Durrant et al , 2003; Watson et al , 2005; Watson et al , 2006a; Duncan et al , 2007; Ullenhag et al , 2007; McGilvray et al , 2009; Simpson et al , 2010). These patients were treated between 1 January 1994 and 31 December 2000; this time period allowed meaningful assessment of the prognostic markers studied.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Baretton et al(1996) reported a poor clinical outcome of patients with non-metastatic colorectal tumors that did not express bcl-2 but showed nuclear accumulation of p53. Watson et al(2005) reported patient stratification by combined p53/bcl-2 phenotype provides stage-independent prognostic information in colorectal cancer. Specifically, that up to a quarter of patients showed a good prognosis p53(−)/bcl-2(+) phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…The colorectal tumour array, produced in house and previously described, was used to analyse tumour binding [33], [34], [35], [36]. Immunohistochemical analysis of 692/29, BR96 and 2-25 LE binding on both arrays was performed using a routine streptavidin-biotin peroxidase method.…”
Section: Methodsmentioning
confidence: 99%